2005
DOI: 10.1097/01.ju.0000181811.61199.35
|View full text |Cite
|
Sign up to set email alerts
|

The Actual Incidence of Bladder Perforation Following Transurethral Bladder Surgery

Abstract: The extravasation of urine (asymptomatic perforation) after transurethral bladder tumor resection may occur much more frequently than believed or reported. It seems that this extravasation does not impose a significant risk of extravesical tumor seeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 16 publications
0
57
0
8
Order By: Relevance
“…6,11 Some degree of drug extravasion in patients undergoing complete, correct TURBT remains unrecognised because cystography is not routine. 34 This might have contributed to the high rate of persistent lower urinary-tract symptoms in our study.…”
Section: Discussionmentioning
confidence: 81%
“…6,11 Some degree of drug extravasion in patients undergoing complete, correct TURBT remains unrecognised because cystography is not routine. 34 This might have contributed to the high rate of persistent lower urinary-tract symptoms in our study.…”
Section: Discussionmentioning
confidence: 81%
“…Initial therapy for bladder perforation is adequate bladder drainage, with only a small percentage of patients requiring surgery (1,3). In patients following TURBT, CT urography is a useful modality to evaluate complications such as perforation and to delineate relevant post surgical anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…Balbay et al demonstrated that up to 58% of TURBTs resulted in contrast extravasation through small and otherwise asymptomatic extraperitoneal perforations. 5 There is no information on the incidence of intraperitoneal perforation. With intraperitoneal perforation, there is a risk of bowel injury.…”
Section: Introductionmentioning
confidence: 99%